Antimicrobial activity of the rhizomes of Curcuma zedoaria (Journal of Bangladesh Academy of Sciences, 2011)
Successive extraction of the dried rhizomes of Curcuma zedoaria Rocs. provided n-hexane, ethyl acetate and methanol extracts. The antimicrobial activity of the different extracts of Curcuma zedoaria was investigated at an initial dose of 500 μg/disc against gram positive, gram negative bacteria and fungi. The methanol extract of the herb showed significant activity against some tested gram negative bacteria. The ethyl acetate extract exhibited moderate activity while the n-hexane showed little activity against some gram negative bacteria.Key words: Curcuma zedoaria; Rhizomes; Antimicrobial activity DOI: 10.3329/jbas.v34i2.6867Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 201-203, 2010